Investigation of the Antioxidant and Antitumour Properties of Some Cyclobutane Ring Containing 2,5-Thiophene Diacyl Compounds - Guler, Alpay; Karatepe, Arzu; Koparir, Pelin; Pekdemir, Sibel; Karatepe, Mustafa (Biointerface Research Applied Chemistry, 2022)
In this research. the effect of thiophene derivatives on the (MDA) concentration which is an indicator of lipid peroxidation. antioxidant vitamins A E and in itro antioxidant activity and antitumor activity, were investigated in cell culture media. In the comparison done among groups. it was observed that MDA and vitamin A concentrations were statistically (P<0,05) changed, Looking at the measured parameters during the experiment. the number of live cells. the compounds is an effective antitumor activity in the L 1210 cell types. The oxidative stress parameters are used for all compounds.
Keywords: HPLC; thiophene; cyclobutane; MDA; antioxidant activity; antitumour activity